Change in pulmonary mechanics and the effect on breathing pattern of high flow oxygen therapy in stable hypercapnic COPD. Issue 4 (19th January 2017) - Pisani, Lara; Fasano, Luca; Corcione, Nadia; Comellini, Vittoria; Musti, Muriel Assunta; Brandao, Maria; Bottone, Damiano; Calderini, Edoardo; Navalesi, Paolo; Nava, Stefano
Abstract : We studied the effects of high flow oxygen therapy (HFOT) versus non-invasive ventilation (NIV) on inspiratory effort, as assessed by measuring transdiaphragmatic pressure, breathing pattern and gas exchange. Fourteen patients with hypercapnic COPD underwent five 30-min trials: HFOT at two flow rates, both with open and closed mouth, and NIV, applied in random order. After each trial standard oxygen therapy was reinstituted for 10 min. Compared with baseline, HFOT and NIV significantly improved breathing pattern, although to different extents, and reduced inspiratory effort; however, arterial carbon dioxide oxygen tension decreased but not significantly. These results indicate a possible role for HFOT in the long-term management of patients with stable hypercapnic COPD. Trial registration number: NCT02363920.